2020
DOI: 10.1097/shk.0000000000001671
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-seq of Human Myeloid-Derived Suppressor Cells in Late Sepsis Reveals Multiple Subsets With Unique Transcriptional Responses: A Pilot Study

Abstract: Background: Increased circulating myeloid-derived suppressor cells (MDSCs) are independently associated with poor long-term clinical outcomes in sepsis. Studies implicate subsets of MDSCs having unique roles in lymphocyte suppression; however, characterization of these cells after sepsis remains incomplete. We performed a pilot study to determine the transcriptomic landscape in MDSC subsets in sepsis using single-cell RNAseq (scRNA-seq). Methods: A mixture of whole blood myeloid-enriched and Ficoll-enriched PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Additionally, we were only able to analyze immune cell transcriptome patterns at one time point in late sepsis. Future transcriptomic analysis with more time points is warranted to analyze time-dependent genomic expression patterns of late sepsis in sepsis survivors (14). Finally, this is a descriptive study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we were only able to analyze immune cell transcriptome patterns at one time point in late sepsis. Future transcriptomic analysis with more time points is warranted to analyze time-dependent genomic expression patterns of late sepsis in sepsis survivors (14). Finally, this is a descriptive study.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the pathobiology of leukocytes in late sepsis, as well as the dysfunctional hematopoiesis that leads to this immune dyscrasia, will be vital to any successful immunomodulation of sepsis survivors. Our laboratory has previously published a pilot study specifically evaluating myeloid-derived suppressor cells in surgical sepsis survivors (14). However, we realized that studies on nonmyeloid immune cell subtypes chronically after sepsis are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing evidence have found that the alternation of microbiota, so-called dysbiosis, may have an impact on the outcome of critically ill patients for at least 3 months [ 7 , 9 , 30 ]. Darden et al used single-cell RNAseq and myeloid-enriched peripheral blood mononuclear cells among critically ill surgical patients on day-21 after the sepsis to characterise the immunosuppressive transcriptome of myeloid-derived suppressor cells in critically ill surgical patients with CCI [ 31 , 32 ]. We speculate that alternation of microbiota might account for the relatively strong association between culture positivity and risk of mortality among non-infectious critically ill surgical patients, including those receiving cardiovascular surgery and patients without malignancy or metastatic tumour (Additional file 1 : Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is a dysregulated systemic inflammatory response, which alters the innate and adaptive immune responses to microbial invasion and results in organ injury with mortality rates of 15–25% 40, 41 . Given significant sepsis disease heterogeneity, single cell transcriptomics offers an valuable approach to provide a better understanding of the molecular mechanisms of sepsis, however, from over 1000 single-cell transcriptomics studies have been published to date 42 , only two studied sepsis 8, 43 . In those two studies, the authors focused on monocytes and myeloid-derived suppressor cells by sorting on specific surface markers.…”
Section: Discussionmentioning
confidence: 99%